Business models in commercial media markets: Bargaining, advertising, and mixing - Miriam Thöne; Alexander Rasch; Tobias Wenzel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We consider a product and a media market and show how a change in the business model employed by the media platforms affects consumers, producers (or advertisers), and price negotiations for advertisements. On both markets, two firms differentiated á la Hotelling compete for consumers. On the media market, consumers can mix between the two outlets whereas on the product market, consumers have to decide for one supplier. With pay-tv, as opposed to free-to-air, mixing by consumers disappears, product prices and advertising rates increase while the number of advertisements declines and media firms' profits increase. These effects are driven by the improved bargaining position of media firms, induced by charging a subscription fee to viewers.
Keywords: L10; D21; L21; 330